Effects of prone positioning on lung mechanical power components in patients with acute respiratory distress syndrome: a physiologic study - Bösing, Christoph; Krebs, Jörg; Conrad, Alice; Otto, Matthias; Beck, Grietje; Thiel, Manfred; Rocco, Patricia R. M.; Lücke, Thomas; Schäfer, Laura Sophie (Critical care, 2024)
Background: Prone positioning (PP) homogenizes ventilation distribution and may limit ventilator-induced lung injury (VILI) in patients with moderate to severe acute respiratory distress syndrome (ARDS). The static and dynamic components of ventilation that may cause VILI have been aggregated in mechanical power, considered a unifying driver of VILI. PP may affect mechanical power components differently due to changes in respiratory mechanics; however, the effects of PP on lung mechanical power components are unclear. This study aimed to compare the following parameters during supine positioning (SP) and PP: lung total elastic power and its components (elastic static power and elastic dynamic power) and these variables normalized to end-expiratory lung volume (EELV). Methods: This prospective physiologic study included 55 patients with moderate to severe ARDS. Lung total elastic power and its static and dynamic components were compared during SP and PP using an esophageal pressure-guided ventilation strategy. In SP, the esophageal pressure-guided ventilation strategy was further compared with an oxygenation-guided ventilation strategy defined as baseline SP. The primary endpoint was the effect of PP on lung total elastic power non-normalized and normalized to EELV. Secondary endpoints were the effects of PP and ventilation strategies on lung elastic static and dynamic power components non-normalized and normalized to EELV, respiratory mechanics, gas exchange, and hemodynamic parameters. Results: Lung total elastic power (median [interquartile range]) was lower during PP compared with SP (6.7 [4.9–10.6] versus 11.0 [6.6–14.8] J/min; P < 0.001) non-normalized and normalized to EELV (3.2 [2.1–5.0] versus 5.3 [3.3–7.5] J/min/L; P < 0.001). Comparing PP with SP, transpulmonary pressures and EELV did not significantly differ despite lower positive end-expiratory pressure and plateau airway pressure, thereby reducing non-normalized and normalized lung elastic static power in PP. PP improved gas exchange, cardiac output, and increased oxygen delivery compared with SP. Conclusions: In patients with moderate to severe ARDS, PP reduced lung total elastic and elastic static power compared with SP regardless of EELV normalization because comparable transpulmonary pressures and EELV were achieved at lower airway pressures. This resulted in improved gas exchange, hemodynamics, and oxygen delivery. Trial registration: German Clinical Trials Register (DRKS00017449). Registered June 27, 2019. https://drks.de/search/en/trial/DRKS00017449
Gesehen am 12.08.2024